Submicronic etched features of silicon with high aspect ratio obtained by cryogenic plasma deep-etching through perforated polymer thin films. Issue 1803 (30th April 2015) - Vital, A.; Boufnichel, M.; Dussart, R.; Gosset, N.; Lefaucheux, P.; Sinturel, C.; Tillocher, T.; Vayer, M.
ABSTRACT: We report the preparation of nanomasks for silicon plasma etching, which is not based on full top-down approaches such as conventional lithographic process. We used laterally phase separated polymers thin films (30 to 100 nm thick) obtained from immiscible polymer blends of poly(styrene) PS and poly(lactide) PLA, PS being the major component, spin-coated onto silicon substrates. Despite the high incompatibility of the two polymers, submicronic domains were obtained in the film. The selective extraction of the minor component (PLA) led to the formation of a perforated layer of PS at the top of the silicon substrate, and was used as a mask for the selective etching of the silicon. For that purpose, we used a cryogenic etching process where the silicon substrate was cooled at a cryogenic temperature (∼ -120°C) and exposed to a monocyclic SF6 /O2 plasma. It was possible to etch anisotropic profiles with vertical sidewalls and minimal defects. Etched feature with an aspect ratio of 7 were obtained in these conditions. We determined that the selectivity of etching (Si/PS) was 11:1, with a silicon etching rate of 0.8 µm/min. The selectivity of these masks was further increased when using the inorganic replicas of the polymer template (50:1) or with chemical modifications of the PS by RuO4 (80:1), allowing for increased aspect ratio etched features (up to 20 in the latter case). Optimized etching processes (such as STiGer process) were also used in order to improve the reproducibility and robustness of the method.